Tolbutamide Eye Drops Increase Aqueous Humor Outflow and Lower Intraocular Pressure: A Proof of Concept for Glaucoma Treatment - Thumann, Gabriele; Sorgente, Nino; Kropp, Martina; Jonescu-Cuypers, Christian Paul (Journal of Ophthalmology and Research, 2021)
Background: Glaucoma refers to a heterogeneous group of diseases characterized by retinal cell degeneration and optic nerve atrophy leading to blindness. Even though about 40% of patients have normal intraocular pressure (IOP), current treatment. focuses on lowering IOP. With time, current drugs become less effective, which has motivated the search for novel drugs.The objective was to establish whether modulators of ATP-sensitive potassium channels influence IOP. Methods: The double-blind, 5-day short duration Proof-Of-Concept study was carried out at the Ophthalmology Clinic, University of Cologne, Germany. The only inclusion criteria were a diagnosis of glaucoma, ability to understand that they would be treated with an experimental drug, and readiness to sign a consent form. Results: In rabbits, 1 h after topical application of 80 µL of 0.5% tolazamide, tolbutamide, glibenclamide, and chlorpropamide suspended in phosphate buffered saline IOP de-creased, whereas 0.5% diazoxide increased IOP. In Cynomolgus monkeys tolbutamide decreased IOP. In 9 glaucoma patients treated for 5 days with one drop of a 0.5% tolbutamide solution twice daily, IOP was an average of 17% lowered. In one patient with ocular hypertension, tolbutamide lowered IOP by a 5-day average of 29% and increased aqueous humor outflow by 185%. No local adverse effects were observed. Conclusions: The data presented show that blockers of the ATP-sensitive potassium channels lower IOP whereas diazoxide, an ATP-sensitive potassium channel opener, increases IOP suggesting that elevated IOP results from an ionic imbalance. The data suggest that sulfonylurea drugs are useful for the treatment of glaucoma.